Impact of genetic polymorphisms on chemotherapy toxicity in childhood acute lymphoblastic leukemia - Gervasini, Guillermo; Vagace, Jose M. (Frontiers in Genetics, 2012)
The efficacy of chemotherapy in pediatric acute lymphoblastic leukemia (ALL) patients has significantly increased in the last twenty years; as a result, the focus of research is slowly shifting from trying to increase survival rates to reduce chemotherapy-related toxicity. At the present time, the cornerstone of therapy for ALL is still formed by a reduced number of drugs with a highly toxic profile. In recent years, a number of genetic polymorphisms have been identified that can play a significant role in modifying the pharmacokinetics and pharmacodynamics of these drugs. The best example is that of the TPMT gene, whose genotyping is being incorporated to clinical practice in order to individualize doses of mercaptopurine. However, there are additional genes that are relevant for the metabolism, activity and/or transport of other chemotherapy drugs that are widely use in ALL, such as methotrexate, cyclophosphamide, vincristine, L-asparaginase, etoposide, cytarabine or cytotoxic antibiotics. These genes can also be affected by genetic alterations that could therefore have clinical consequences. In this review we will discuss recent data on this field, with special focus on those polymorphisms that could be used in clinical practice to tailor chemotherapy for ALL in order to reduce the occurrence of serious adverse effects.